2014
DOI: 10.1021/jp412461q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction Mechanism of Polytetrafluoroethylene on Aluminum Surface under Friction Condition

Abstract: To develop a novel shearing resin material, it is necessary to understand the mechanism of friction-induced chemistry during the friction process. For this purpose, the chemical reaction of the polytetrafluoroethylene (PTFE) resin on an aluminum surface during friction was first focused on and investigated by a quantum chemical molecular dynamics method. From our simulation, an aluminum atom on a native oxide of aluminum surface led to a tribochemical reaction, which included defluorination of PTFE and aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 33 publications
(48 reference statements)
5
51
0
Order By: Relevance
“…A second limitation is that IR measurements were conducted in lab air, which prevented us from removing all water sources. It is possible that radicals formed in the inert environment were stable until being eventually exposed to air; this does not explain why the system transitioned to low wear and formed brown 22 surfaces early during sliding in dry conditions, however. We believe that trace contamination in the environment or the sample must have provided enough fuel to start but the processes but not enough fuel to sustain a low wear condition.…”
Section: Ir Spectroscopymentioning
confidence: 98%
See 1 more Smart Citation
“…A second limitation is that IR measurements were conducted in lab air, which prevented us from removing all water sources. It is possible that radicals formed in the inert environment were stable until being eventually exposed to air; this does not explain why the system transitioned to low wear and formed brown 22 surfaces early during sliding in dry conditions, however. We believe that trace contamination in the environment or the sample must have provided enough fuel to start but the processes but not enough fuel to sustain a low wear condition.…”
Section: Ir Spectroscopymentioning
confidence: 98%
“…The beneficial effects of environmental moisture on wear rate strongly suggest a tribochemical mechanism 12, 20 of wear reduction. 4 Onodera et al [21][22] used computational simulations to elucidate the role of environment and chemistry on the tribological performance of this material system. They proposed that end-chain carboxyl groups (R-COOH) were likely formed in humid environments and suggested that these groups improve bonding of the PTFE to the counterface; stable and well-adhered transfer films reduce wear by preventing the need for subsequent transfer 1 .…”
Section: Introductionmentioning
confidence: 99%
“…To help elucidate the effect of water vapor on the wear of PTFE nanocomposites, Onedera et al [47,48] used computational tools to identify possible tribochemical reactions between PTFE and environmental moisture during sliding; based on the results, they proposed that PTFE end-chain carboxyl groups formed to help bond PTFE transfer films to the counterface. In 2015, Pitenis et al [29] and Harris et al [27] conducted spectroscopic studies on transfer film chemistry of the same low wear alumina PTFE nanocomposite.…”
Section: Chemistry Of the Transfer Filmmentioning
confidence: 99%
“…19,20 Kubo and co-workers developed a tightbinding quantum chemical molecular dynamics (TB-QCMD) simulator and successfully applied it to various tribochemical reaction studies. 21,22 Although very accurate in describing the chemical reactions, the computational cost of the first-principles molecular dynamics is substantial, limiting the usage of this method with relatively small spatial and time scales. As an alternative, there is also a significant trend in recent years on the development and application of reactive force fields (RFF) in molecular dynamics simulations, which can account for chemical bond forming and bond breaking in a computationally efficient way.…”
Section: Introductionmentioning
confidence: 99%